2019
DOI: 10.1371/journal.pone.0225519
|View full text |Cite
|
Sign up to set email alerts
|

Face recognition and memory in congenital amusia

Abstract: Congenital amusia, commonly known as tone deafness, is a lifelong impairment of music perception and production. It remains a question of debate whether the impairments in musical domain observed in congenital amusia are paralleled in other non-musical perceptual abilities. Using behavioral measures in two experiments, the current study explored face perception and memory in congenital amusics. Both congenital amusics and matched controls performed a face perception task (Experiment 1) and an old/novel object … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
0
6
0
1
Order By: Relevance
“…These studies show that there is a strong correlation between language and music related to the development of skills in these two domains and their cognitive processing, independent of formal musical training [77][78][79]. Other researchers highlight how music perception influences language acquisition [80], is linked to spatial processing, visual memory and speech perception [81][82][83] and how the structural redundancy of speech and musical communication shapes the individual's perceptual abilities [84,85]. Moreover, neuroimaging experiments document how music and language are processed in the same areas of the brain and in similar ways, on the basis of their syntactic integration mechanisms [86,87].…”
Section: Twin Studies Heritability and Hints To The Neuropsychology Of Musicmentioning
confidence: 95%
“…These studies show that there is a strong correlation between language and music related to the development of skills in these two domains and their cognitive processing, independent of formal musical training [77][78][79]. Other researchers highlight how music perception influences language acquisition [80], is linked to spatial processing, visual memory and speech perception [81][82][83] and how the structural redundancy of speech and musical communication shapes the individual's perceptual abilities [84,85]. Moreover, neuroimaging experiments document how music and language are processed in the same areas of the brain and in similar ways, on the basis of their syntactic integration mechanisms [86,87].…”
Section: Twin Studies Heritability and Hints To The Neuropsychology Of Musicmentioning
confidence: 95%
“…They used three datasets: AR Face, YALE and SDUM-LA-HMT [6]. Further research on FR can be found in [7][8][9][10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They used three datasets: AR Face, YALE and SDUMLA-HMT [6]. Further research on FR can be found in [7][8][9][10].…”
Section: Literature Reviewmentioning
confidence: 99%